Die another day [videorecording (Blu-Ray)] - Broccoli, Albert R., 1909-1996; Wilson, Michael G., 1942-; Broccoli, Barbara, 1960-; Purvis, Neal; Wade, Robert, 1961-; Tamahori, Lee; Brosnan, Pierce; Berry, Halle; Stephens, Toby, 1969-; Pike, Rosamund, 1979-; Yune, Rick, 1971-; Cleese, John; et al. (Distributed by 20th Century Fox Home Entertainment, 2008)
British secret agent, 007 James Bond, is sent to North Korea to infiltrate the renegade military unit under officer Colonel Moon. The mission is sabotaged. Colonel Moon is killed and his second-in-command Zao is injured. James is captured, tortured and interrogated. 14 months later, Bond is released and traded for Zao. James' boss, M, relieves him of his 007 status. James sets out to get his revenge against those who set him up. He tracks down Zao in Cuba where he is receiving a facial reconstruction operation to give him a new identity. James finds diamonds on Zao and those lead him to British billionaire Gustav Graves. With help from sexy American secret agent Jinx and Grave's publicist, undercover M:I-6 agent Miranda Frost. James sets out to stop Graves who is working with Zao on using Icarus, a laser-beam directed machine, as a weapon of mass destruction.